2019
DOI: 10.1101/725762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesterol is a strong promotor of an α-Synuclein membrane binding mode that accelerates oligomerization

Abstract: Dysregulation of the biosynthesis of cholesterol and other lipids has been implicated in neurological diseases, including Parkinson's disease, where the misfolding of membraneassociated α-Synuclein is a key molecular event. Recent research also suggests that α-Synuclein aggregation is influenced by the lipid environment. The exact molecular mechanisms responsible for cholesterol’s effect on α-Synuclein binding to lipids and how this binding may affect α-Synuclein oligomerization and fibrillation remain elusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…A recent study reported that cholesterol modulates the conformational state of α-Syn and accelerates its oligomerization [ 99 ]. The treatment of neuronal culture with cholesterol results in excessive α-Syn aggregation.…”
Section: Obesity Hypercholesterolemia and Pdmentioning
confidence: 99%
“…A recent study reported that cholesterol modulates the conformational state of α-Syn and accelerates its oligomerization [ 99 ]. The treatment of neuronal culture with cholesterol results in excessive α-Syn aggregation.…”
Section: Obesity Hypercholesterolemia and Pdmentioning
confidence: 99%
“…Recently, surface plasmon resonance (SPR) was employed to measure the binding of αSyn monomers to lipid vesicles and this resulted decreased with the addition of cholesterol molecules to the membrane composition. The effect was detected also in the presence of negatively charged vesicles ( Jakubec et al, 2019 ). A very recent publication from Fusco and coworkers confirmed these results showing by CD experiments that αSyn binding is reduced in the presence of cholesterol.…”
Section: Effect Of the Biological Environment On αSyn Structural Featuresmentioning
confidence: 88%
“…At the same time, Jakubec et al questioned whether cholesterol could influence αSyn fibrillation and they observed that the aggregation was effectively promoted by analyzing ThT (thioflavin T) and TPE-TPP (bis(triphenylphosphonium) tetraphenylethene) fluorescence assays. This outcome could be explained taking into consideration that cholesterol could act as a nucleation site ( Jakubec et al, 2019 ).…”
Section: Effect Of the Biological Environment On αSyn Structural Featuresmentioning
confidence: 99%
“…As new developments in this field continues to emerge, the need for The SMALP platform enables us to obtain equally informative snapshots from surroundings of membrane proteins; however, it requires more improvement to a need for engineering the amphipathic polymers for formation of larger nanodiscs. Other analytical approaches such as EPR [ 92 ], Fluorescence-based methods (FRET/BRET) [ 93 ], surface plasmon resonance (SPR) [ 94 ], SAXS, and NMR have been utilized to shed light on lipid dependent protein-protein interaction in the lipid bilayer, receptor oligomerizations/regulation and lipid-dependent oligomerization of essential peripheral membrane proteins (such as α-synuclein and Amyloid precursor protein (APP) peptides) [ 72 , 88 ], in polymer-based nanodiscs. The size and lipid composition of nanodiscs are well-controlled during the preparation of LUV vesicles.…”
Section: Synthetic Polymers For Reconstitution Of Membrane Assembliesmentioning
confidence: 99%